The Impact of Total Quality Management to development and Improvement Health Services at Rniah General Hospital provide: دراسة تطبيقية - د : جعفر عبد الله موسى إدريس (White Nile Journal for Studies and Research, 2015)
The Objective of this research is to define the impact of using Total Quality Management to develop and improvement of health services at Rniah General hospital to provide a conceptual framework that identifies and defines the various concepts related to the management of the overall quality of health services. especially the philosophy of the zero defect. identify the level of quality of health services. which means to satisfy patients and their families by meeting requirements of treatment for them provide appropriate care for patients and good handling patients and visitors. The study assumes that Rniah General Hospital brought about improvements in the quality of health services with TQM through the performance of its administrative activity and therapeutic The success of the hospital and its development depends on the extent of their ability to provide good health services and without errors Zero defect to meet the needs and desires of customers (patients) which is depending on the level of quality of health service